1999
DOI: 10.1097/00006534-199909040-00008
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Approach for Increasing the Survival of Autologous Fat Grafts in the Treatment of Contour Defects

Abstract: Autologous fat grafting as a technique to correct soft-tissue defects is a controversial subject. The high percentage of fat resorption and the resulting need for additional grafting considerably reduce the value of this method. The purpose of this study was to evaluate the clinical application of tissue-culturing methodology in the handling of the lipocyte aspirate in an endeavor to improve the survival rate and therefore the take of the grafted lipocytes. The method consists of syringe aspiration of the lipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 18 publications
1
22
1
Order By: Relevance
“…The treatment of tissue loss with grafting of autologous adipose tissue in the aesthetic areas is not a widely used technique in plastic and reconstructive surgery; [1,2] as a matter of fact, general literature reports conflicting studies on the use of this procedure for tissue replacement [8-18]. …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The treatment of tissue loss with grafting of autologous adipose tissue in the aesthetic areas is not a widely used technique in plastic and reconstructive surgery; [1,2] as a matter of fact, general literature reports conflicting studies on the use of this procedure for tissue replacement [8-18]. …”
Section: Discussionmentioning
confidence: 99%
“…However, other studies have achieved good results with grafting of autologous adipose tissue in areas previously exposed to radiation therapy, although they reported that resorption was slightly superior to normal tissues [1]. In order to reduce the aesthetic impact resulting from tissue resorption, it is advisable to plan a 20–50% hypercorrection of the grafted tissue [7].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations